2017
DOI: 10.21521/mw.5681
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amines in rennet ripening cheeses as a health risk to consumers

Abstract: SummaryBiogenic amines are nitrogen compounds which are products of the decarboxylation of free amino acids. They are produced with the participation of bacterial microflora producing enzymes, and they may be introduced together with food into the human body. The highest amounts of biogenic amines are found in meat, fish and cheeses. Consumption of products containing biogenic amines can cause food poisoning and allergies in consumers. The most common amines in cheeses are tyramine, histamine, putrescine, cada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(62 reference statements)
0
1
1
Order By: Relevance
“…Given that the toxic threshold dose for histamine in cheeses has been temporarily established at 400 mg/kg (29), it was found that the amine content exceeded this value in Gorgonzola cheese after 28 and 42 days of storage at 22°C, where its levels reached 400.29 ± 10.13 and 730.47 ± 20.01 mg/kg, respectively, and reached this toxicity level in Camembert cheese on day 112 stored at 4°C (405.21 ± 30.06 mg/kg). The wide variability of histamine concentration in different cheeses may depend on type of cheese, ripening time, conditions of manufacturing process, and bacterial starter culture used (16,20,21). In the present study less histamine was detected in hard cheeses than soft ones and its amount was low (in a range from below the limit of detection to 35.84 ± 4.12 mg/kg).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Given that the toxic threshold dose for histamine in cheeses has been temporarily established at 400 mg/kg (29), it was found that the amine content exceeded this value in Gorgonzola cheese after 28 and 42 days of storage at 22°C, where its levels reached 400.29 ± 10.13 and 730.47 ± 20.01 mg/kg, respectively, and reached this toxicity level in Camembert cheese on day 112 stored at 4°C (405.21 ± 30.06 mg/kg). The wide variability of histamine concentration in different cheeses may depend on type of cheese, ripening time, conditions of manufacturing process, and bacterial starter culture used (16,20,21). In the present study less histamine was detected in hard cheeses than soft ones and its amount was low (in a range from below the limit of detection to 35.84 ± 4.12 mg/kg).…”
Section: Discussioncontrasting
confidence: 46%
“…This intoxication manifests itself in headaches, hypotension, vomiting, diarrhoea, cramping, skin rashes and swellings (3). Histamine is degraded in the body by oxidative deamination catalysed by monoamine and diamine oxidases (21,26). However, after ingestion of food with high concentrations of histamine, in the absence or scarcity of these enzymes (e.g.…”
Section: Introductionmentioning
confidence: 99%